SPIRITUALITAS LESBIAN DI KOTA MAKASSAR - Sulaiman, Ramlah; Ahmad, M. Ridwan Said (Citra Media Publishing, 2024)
This research aims to determine social problems, especially lesbian sexual deviance activities in the city of Makassar. The method used in this research is a qualitative method with a descriptive approach and took the research location in the city of Makassar. The subjects of this research were people involved in lesbian sexual deviance activities, especially students using a qualitative approach. Data collection was carried out using interview and observation methods. We then discussed the results of the observation and interview activities together and then the results of the research showed that lesbian sexual deviance activities were mostly carried out by teenagers, students and students with the main factors that encourage them to get involved in lesbianism activities, namely broken home situations, social environment, promiscuity, and past traumatic experiences.